1997
DOI: 10.1177/009102609702600111
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Organization-Based Self-Esteem on Workplace Outcomes: An Examination of Emergency Medical Technicians

Abstract: Forty-six technicians employed by an ambulance and life flight service were surveyed to examine the effects of organization-based self-esteem (OBSE) on career outcomes and quality. Results show that those high in OBSE reported stronger career commitment and weaker career withdrawal intentions than those low in OBSE. Contrary to predictions, significant differences were not found for career satisfaction and career tenure. However, there was a significant difference between the high and low groups on the import … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
1
18
0
2
Order By: Relevance
“…Referring to the workplace, Carson et al (1997) and Stajkovic and Luthans (1998) defined self-efficacy as a kind of taskbased self-esteem, and the individual's conviction (or confidence) about his or her abilities to mobilize the motivation, cognitive resources, and courses of action needed to successfully execute a specific task within a given context. According to Maslow's Needs Hierarchy Theory, the need for self-esteem is at the high needs level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to the workplace, Carson et al (1997) and Stajkovic and Luthans (1998) defined self-efficacy as a kind of taskbased self-esteem, and the individual's conviction (or confidence) about his or her abilities to mobilize the motivation, cognitive resources, and courses of action needed to successfully execute a specific task within a given context. According to Maslow's Needs Hierarchy Theory, the need for self-esteem is at the high needs level.…”
Section: Discussionmentioning
confidence: 99%
“…Concepts of self, and the closely related constructs of self-image and self-esteem, influence a person's general outlook on life. In fact, Carson et al (1997) also suggested that self-efficacy is some kind of task-based self-esteem. Somehow, self-efficacy and self-esteem are very similar (Haycock et al, 1998).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Individuals with higher self-esteem tend to see more positive effects from their work than individuals with lower self-esteem (Chandler & Lee, 1997). Also, perceived worth in one setting encourages perceived worth in others (Carson & Carson, 1997). Individuals with higher self-esteem are more likely to recognize nontraditional career options and the career potential attached to their skills and contacts (Super, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that OBSE significantly influenced job satisfaction among IT developers [28]. In addition, Carson et al [6] predicted that OBSE is positively related to career satisfaction. Perceived OBSE may be interpreted as a cue from the organizational environment about the value placed on the work or the professional and thus positively influences career satisfaction.…”
Section: Organization-based Self-esteem (Obse)mentioning
confidence: 99%